A ética do desejo : estudo etnográfico da formação de psicanalistas em escolas lacanianas de psicanálise - Antonio, Maria Carolina de Araujo (Universidade Federal de São Carlos, 2015)
These researche approaches the relation between the construction of the person and the production of knowledge operated by/in lacanian psychoanalysis, as theory and therapeutical practice, through etnographic description of the training process of psychoanalisis. The field work was done in psychoanalytic institutions that follows the framework of School (created by Jacques Lacan), in São Paulo and Buenos Aires, in which it was possible to observe the institutional organization, its devices of training and to establish interlocution with its members and its “students”. The psychoanalytic institutional movement conjugates centralization and segmentation of power/knowledge in the production of its leaderships, wich were constituted by a kind of “master-analyst/disciple-analysant” relation set dawn in the transmission of the clinical expertise. The lacanian institutions is organized hierarchically, based in the differential classification of the members, in accordance with the distribution of the title of psychoanalyst between them. Through a ritual procedure, the process of analyst formation is witnessed for al the analytical community, which confers meaning to the associative experience and proves the therapeutical effectiveness in the construction of new models of subjectivation. Taking as reference the conception of the interlocutors about the professional vocation as related with the submission to the analytical experience, was problematized the articulation between psychoanalytic theory and therapeutical practice in the construction of processes of individuation and psychological realities in the terapeutical process. Psychoanalyzes is seen here as mixture of science, belief, philosophy, and guided by dualism thougths as nature/culture, body/soul, conscious/unconscius, subject/object. Although the lacanians members of the School demand a statement of rationality specific to psychoanalysis and critic of the psychiatric knowledge, they updated, on other ways, aspects of the hegemony, control and authority of the medical knowledge in public ou private clinical attendance of yours patients. With the proposal to accomplish an anthropology of psychoanalysis, were considered emic categories as “subject of desire”, “analytic cause”, “ethics of desire” and “politics of psychoanalysis” to understand the relations and the meanings articulated for the professional experience, the clinical practice and the statute of psychoanalysis in the mental health context by the lacanians members of the School.
The ethics of desire : etnographic study of the training analysts in lacanianain’s schools of psychoanalysis.
Keywords: Antropologia social; Pessoa; Produção de conhecimento; Psicanálise lacaniana; Saúde mental; Construction of the person; Knowledge production; Lacanian psychoanalysis; Mental health; CIENCIAS HUMANAS::ANTROPOLOGIA::TEORIA ANTROPOLOGICA